Pengembangan Promosi Digital UMKM Agen Markisah Gindo Rajo di Sumatera Barat - Nada Merliana Habillah Putri; Alfino Daffa Mehendri; Fikra Hafidesko Maltra; Novadilastri .; Sularno . (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in supporting regional economic growth by creating employment opportunities, developing local products, and improving community welfare. One of the MSMEs with considerable development potential is Agen Markisah Gindo Rajo in West Sumatra, which specializes in selling passion fruit and its processed products. Although the business offers high-quality products, its promotional activities still need to be improved to reach a broader market. This study aims to examine digital promotion development as a strategy to enhance the existence and competitiveness of Agen Markisah Gindo MSME. The research employed observation, interviews, and documentation to collect information regarding business conditions, marketing strategies, and opportunities for digital promotion. The findings indicate that digital media can serve as an effective strategy to introduce products to the public, expand market reach, and improve MSME competitiveness in the digital era.